2019
DOI: 10.1016/j.sxmr.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Deep Dyspareunia: Review of Pathophysiology and Proposed Future Research Priorities

Abstract: Introduction: Dyspareunia has been traditionally divided into superficial (introital) dyspareunia and deep dyspareunia (pain with deep penetration). While deep dyspareunia can co-exist with a variety of conditions, recent work in endometriosis has demonstrated that coexistence does not necessarily imply causation. Therefore, a reconsideration of the literature is required to clarify the pathophysiology of deep dyspareunia. Aims: To review the pathophysiology of deep dyspareunia, and to propose future research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 159 publications
0
20
0
2
Order By: Relevance
“…Women with dyspareunia experience orgasm less often, which is correlated with a decrease in reported overall well-being [13]. There are several promising avenues for exploration of the pathophysiology and treatment of deep dyspareunia [14].…”
Section: Introductionmentioning
confidence: 99%
“…Women with dyspareunia experience orgasm less often, which is correlated with a decrease in reported overall well-being [13]. There are several promising avenues for exploration of the pathophysiology and treatment of deep dyspareunia [14].…”
Section: Introductionmentioning
confidence: 99%
“…The differentiation of sexual pain by type was also a strength, given that deep and superficial dyspareunia are often measured in aggregate. 1 In addition, sampling and nonresponse error were unlikely to have biased the results, given the low rates of partial questionnaire completion (Figure 1, Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis is known to cause deep dyspareunia, which is defined as pelvic pain occurring with deep penetration during sexual activity. 1 Women with endometriosis may also experience superficial dyspareunia, or pain at the vaginal introitus, as a consequence of comorbidities such as provoked vestibulodynia or pelvic floor dysfunction. 2,3 Deep and superficial dyspareunia seem to co-occur in populations seeking tertiary care; in 1 study approximately 40% of women with dyspareunia reported both types of pain.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common syptoms associated with its appearance is dyspareunia, defined as recurrent or persistent genital pain during sexual intercourse [2]. In women, dyspareunia is labeled as "deep" or "superficial", depending on whether it appears on vaginal introitus at the beginning of the penetration or within the pelvis when penetration is deeper, respectively [3]. Dyspareunia has been estimated to affect between 8% and 21.1% of the worldwide population, a value that is highly variable among countries [4].…”
Section: Introductionmentioning
confidence: 99%